EAP-Based Authentication for Ad Hoc Network - Muhammad Agni Catur Bhakti; Azween Abdullah; Low Tan Jung (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2007)
Wireless network has been deployed worldwide, but some security issues in wireless network might haveprevented its further acceptance. One of the solutions to overcome the limitation of wireless network security isthe IEEE 802.1X specification, a mechanism for port-based network access control, which is based onExtensible Authentication Protocol (EAP). It is an authentication framework that can support multipleauthentication methods. EAP can run over many types of data-link layer and it is flexible in its implementation.Thus, it might be possible to use EAP as a generic authentication mechanism in various wireless networks,including ad hoc network. This paper describes possible use of EAP in ad hoc network and proposes amechanism / approach to implement EAP in ad hoc network using EAP multiplexing model with master node asauthentication server.Keywords: Authentication, IEEE 802.1X, Extensible Authentication Protocol (EAP), ad hoc.